Rheology and phase behavior of aggregating emulsions related to droplet-droplet interactions - Berli, Claudio Luis Alberto (2007)
The present work deals with the relationship between colloidal interactions and physical properties of emulsions, in particular rheology and gel transition. Experimental data on protein-stabilized oilin- water emulsions are considered. In this system, the excess of protein in the aqueous phase yields reversible droplet aggregation by the mechanism of depletion. Thus both phase and flow behaviors can be controlled by changing protein concentration, ionic strength and temperature. Calculations of the potential of interaction between droplets are carried out in the framework of colloid science. Particular emphasis is placed on the role that droplet-droplet interaction plays in defining the morphology of the aggregates, hence the microstructure and finally, the bulk physical properties. This understanding offers new perspectives in the study of complex food systems.